Potential Health Benefits of Fruits and Vegetables - Mazzoni, Luca; Fernández, Maria Teresa Ariza; Capocasa, Franco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As plant-based foods, both vegetables and fruits have been clearly associated with the presence of high amounts of bioactive compounds, and have been demonstrated as having a central role in the prevention of diseases. Many scientists of different research fields have lavished great effort both to characterize the bioactive compounds' compositions and to deepen understanding regarding the mechanisms of action through which fruits and vegetables exert their health-promoting and/or disease-preventing properties. In this book, studies on the bioactive compounds' composition of the main fruit and vegetable species, on their health effects as fresh-consumed, transformed products or applied in in vitro models, and on their mechanisms of actions against human pathologies are presented.